Prevalence of Cataract and Risk Factors in Al-Kharj, Saudi Arabia (Asian Journal of Pharmaceutics (AJP), 2024)
Introduction: Cataracts are a leading cause of blindness, predominantly affecting the elderly. This study aims toestimate the prevalence of cataracts in Al-Kharj, Saudi Arabia, and identify associated risk factors and demographiccharacteristics. Method: The study is a cross-sectional survey conducted for patients over 18 years old. Thepatients’ demographics and medical history, including cataract diagnosis and risk factors, were collected andanalyzed using Statistical Package for the Social Sciences. Statistical tests included the Chi-square for categoricalvariables and the t-test for continuous variables, with significance set at P < 0.05. Results: The study sampleconsisted of 100 participants, with a female majority (59%) and a significant proportion of individuals over67 years old (37%). Nuclear cataracts were the most common (80%), followed by cortical (36%) and posteriorsubcapsular (PSC) cataracts (27%). Significant associations were found between diabetes and PSC cataracts(P = 0.027), and between age and cataract grade (P < 0.001). Smoking and hypertension also showed significantcorrelations with cataract types. Conclusion: Age, diabetes, hypertension, and smoking are significant risk factorsfor cataracts in Al-Kharj. Nuclear cataracts are the most prevalent, especially in individuals over 67 years old. Theassociations between cataracts (types and grades) and risk factors such as diabetes, smoking, and hypertensionshould be considered. Addressing risk factors could reduce cataract-related visual impairment.